Praktik Metode Resitasi dalam Pembelajaran Al-Qur’an Hadist - Sefiana, Siska Dwi; Hidayati, Eka Wahyu; Ulul Albab, Hayyan Ahmad (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2025)
The recitation method is very important to use in the teaching and learning process, especially in the Al-Qur'an Hadith subject. The use of the recitation method in learning Al-Qur'an Hadith as a reinforcement in understanding the material and students can deepen understanding and increase activity. By using the recitation method, students can stand alone without the help of others. This research aims to explain how teachers apply Al-Qur'an Hadith learning using the recitation method. Explain how students practice the recitation method in learning Al-Qur'an Hadith. This type of research is descriptive qualitative. This research was conducted at MTs Nurul Huda Suci Sugio. Data collection techniques use observation, interviews, documentation. The data analysis technique uses the Miles and Huberman method. The results of the first research show that teachers apply the recitation method in learning Al-Qur'an Hadith by giving directions to students and seeing the extent of their ability to read Hadith about studying. The recitation method has proven to be effective because students can better understand and appreciate the tasks given, and show satisfactory learning results. Both recitation methods are effective in learning because students can deepen and appreciate the material that has been given. This assignment method creates a clear teaching and learning interaction format, where assignment completion can be done individually or in groups according to the instructions given by the teacher.